How to combat littering: An analysis with a focus on the Czech Republic - Vít Hinčica (Economic and Environmental Studies (E&ES), 2018)
The work attempts to comprehend why littering is so extensive and, with the use of several findings provided in Gary S. Becker's article entitled 'Crime and Punishment: An Economic Approach', to explain why under current conditions more waste discarded in the environment can be expected. The article was created from the perspective of the Czech Republic, where the author lives. He analysed some past research carried out by other scientists and institutions from all over the world, and he was also observing the situation in different Czech regions in order to approximately learn how large the problem with littering in his country is and what kind of litter can be found in the Czech nature. Afterwards, the author decided to address the Ministry of the Environment of the Czech Republic so as to learn what measures were planned to be taken in order to significantly reduce littering. As a result of all this, the author himself decided to pay special attention to beverage containers and proposed to impose mandatory deposits on them in order to reduce the volume of litter that can be found out of the appropriate places. The author, basing his arguments on findings of other authors, gets to the conclusion that such a measure - provided that some conditions are respected - can work anywhere in the world, beverage containers not being the only type of litter suitable for this step.
Keywords: A11; B41; Q01; Q53; Q58; 330; littering; deposit; beverage container; Czech Republic; environment